Infinity ankle arthroplasty with traditional instrumentation and PSI prophecy system: preliminary results - Giardini, Piero; Di Benedetto, Paolo; Mercurio, Domenico; Gisonni, Renato; Molinari, Marco; Causero, Araldo; Cortese, Fabrizio (Acta Biomedica Atenei Parmensis, 2020)
Ankle arthrodesis has been considered the surgical Gold Standard for advanced ankle arthritis; prosthetic replacement of the tibio-talar joint played a secondary role.The introduction of last generation ankle prostheses lead to better outcome and a lower rate of complication.PSI represents the most recent innovations introduced on the market of ankle arthroplasty:PSI is proposed as a surgical technique capable of making ankle arthroplasty more accurate and more reproducible compared to standard referencing guidesAim of the study is to report early clinical and radiographic outcomes obtained from a single surgeon experience by implanting the same ankle prosthesis using a standard (STD) or a PSI instrumentationUnlike no difference in the average increment of normalized sub score related to function in each group (PSI vs STD), the analysis of normalized pain sub score pointed out a greater average improvement in the PSI group(+75%)compared to the STD group(+62%);this result has been adovacated to the absence of post operative gutter impingement syndrome in the PSI group compared to the STD referencing group.The analysis of radiographic angles revealed a more accurate and reproducible positioning of the components in the PSI group; ankle arthroplasty performed with PSI reported a reduction of both surgical times and the need of intraop.fluoroscopy.PSI ankle arthroplasty achived more accurate and reproducible clinical and radiographic results compared to STD instrumentation;long-term follow-up are needed to demonstrate whether a better positioning of the implant is associated with an increased survival of the prosthesis and therefore justifies the additional costs of PSI.